Optimasi Keuntungan Menggunakan Model Linar Programming Metode Simpleks Pada Umkm Di Kabupaten Bandung - Damayanti, Astuti; Evi Sopiati (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This research is motivated by the importance of resource efficiency in MSMEs to increase competitiveness in the footwear manufacturing industry. The objective of this study is to determine the optimal production mix combination between Regular Sneakers and Premium Sneakers to maximize profits at UMKM Jrnieet Shoes. The research method used is quantitative with a Linear Programming model using the Simplex algorithm, supported by POM-QM software for calculation accuracy. The key findings show that the optimal solution is achieved by producing 150 units of Regular Sneakers and 95 units of Premium Sneakers per month, generating a maximum profit of IDR 35,461,450. Furthermore, it was found that local leather raw material is the main binding constraint that most affects profitability. Price adjustments for premium products are also recommended to balance the company's profit margins.